2022
DOI: 10.3389/fmars.2022.989325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium humate and probiotics on growth performance enzyme activity and microbial environment of Litopenaeus vannamei in high-density zero‐water exchange systems

Abstract: The study investigates the outcomes of adding sodium humate and sodium humate with probiotics (Lysinibacillus, Bacillus subtilis) to culture water on the growth performance, enzyme activity, and microbial environment of shrimp. The sodium humate and probiotics concentrations were 3 mg/L and 105 CFU/mL in the culture water. Litopenaeus vannamei (0.31 ± 0.03 g) at a density of 300 shrimps/m3 were cultured in nine buckets for a 43-days culture experiment. The results showed that the survival rate (SR) of L. vanna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
(59 reference statements)
1
1
0
Order By: Relevance
“…Several bacterial genera, such as Vibrio, Marivita, ZOR0006, Roseobacter, Ruegeria, Psychromonadaceae, Edwardsiella, Clostridium sensu stricto 1, Halioglobus, and Shimia, were predominated in the gut of shrimps. Of these genera, Vibrio, Marivita, and Roseobacter were found to be increased in the A. nigerfed shrimps, which is almost consistent with the previous findings (Li et al, 2019;Liao et al, 2022). Roseobacter 27-4 is a probiotic bacterium for protecting turbot (Scophthalmus maximus) larvae against Vibrio anguillarum (Planas et al, 2006).…”
Section: Sharma Et Al (2022) Indicated Thatsupporting
confidence: 89%
“…Several bacterial genera, such as Vibrio, Marivita, ZOR0006, Roseobacter, Ruegeria, Psychromonadaceae, Edwardsiella, Clostridium sensu stricto 1, Halioglobus, and Shimia, were predominated in the gut of shrimps. Of these genera, Vibrio, Marivita, and Roseobacter were found to be increased in the A. nigerfed shrimps, which is almost consistent with the previous findings (Li et al, 2019;Liao et al, 2022). Roseobacter 27-4 is a probiotic bacterium for protecting turbot (Scophthalmus maximus) larvae against Vibrio anguillarum (Planas et al, 2006).…”
Section: Sharma Et Al (2022) Indicated Thatsupporting
confidence: 89%
“…In line with results obtained for dairy bulls [ 61 ], higher AMS activities were shown in the intestines and liver of the SO groups, which indicates that dietary SO could enhance carbohydrate utilization in largemouth bass [ 62 ]. As the dominant enzyme in lipolysis, variations in LPS activities can reflect the animal’s ability to use lipids [ 63 ]. In this study, we found that there were lower LPS activities in the intestines and liver tissues in the LO trial groups, which is in line results found with red swamp crayfish [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudohongiella and Catenovulum were dominant genera in the PB systems. Pseudohongiella can enhance the transfer of organic matter and metabolism to increase its utilization [36]. Catenovulum, a common marine probiotic, can degrade proteins and polysaccharides and increase the resistance of aquatic organisms to Vibrio [37].…”
Section: Discussionmentioning
confidence: 99%